Intravenous Immunoglobulin Inhibits Liver Cancer Progression by Promoting p38MAPK-Associated Apoptosis. (14th July 2022) - Xu, Fengjie; Lin, Runzhui; Liu, Jianrui; Chen, Zeming; Zhuo, Hua; Liu, Xingmu
Abstract : Objective . The aim of this study is to explore the effect of intravenous immunoglobulin (IVIG) on the development of rat hepatocellular carcinoma and its possible molecular mechanism. Methods . Sixty adult male Sprague-Dawley (SD) rats were randomly divided into three groups: control, diethylnitrosamine(DEN) + normal saline(NS), and DEN + IVIG groups, with 20 rats in each group. The rats in the DEN + NS group and DEN + IVIG group were given DEN 0.2 g/kg intraperitoneal injection once on day 1 and then 0.05% DEN aqueous solution in drinking water to establish a rat liver cancer model. Immunoglobulin (IgG) was injected intraperitoneally into the DEN + IVIG group twice a week at the dose of 100 mg/kg, and saline was administered intraperitoneally into the control group at a 50 mg/kg dosage. The body weight of each group of rats was recorded twice a week. All treatments were maintained continuously for 12 weeks. After the intervention, the liver function indexes of rats were measured by a fully automated biochemical analysis instrument. The liver histopathology was observed by hematoxylin-eosin(HE) staining. Immunohistochemistry was used to detect c-myc protein expression, and Western blotting was used to determine p38MAPK and p-p38MAPK protein expressions, as well as apoptosis-related proteins such as Bcl-2, Bax, and cleaved caspase-3. Results . Compared with the rats in the DEN + NS group, rats in the DEN + IVIG group showed substantially higher body mass (P < 0.05 ), higher survival rate (P < 0.05 ), and lower liver function indexes (P < 0.05 ). Few focal necrosis of cancer cells and few nuclear division were observed in the rats in the DEN + IVIG group. The rats in the DEN + NS group showed lamellar necrosis of cancer foci, destruction of normal liver lobular structure, and hepatocellular carcinoma cells. Immunohistochemical analysis results revealed that the expression of c-myc was reduced in the DEN + IVIG group (P < 0.05 ), and Western blotting confirmed that the Bcl-2 expression was decreased (P < 0.05 ), while Bax, p38 MAPK, p-p38 MAPK, and cleaved caspase-3 protein expressions were increased (P < 0.05 ). Conclusion . IVIG prophylactic injection can delay tumor development and induce apoptosis in primary hepatocellular carcinoma in rats. The mechanism is connected to the activation of the p38MAPK signaling pathway by upregulating the level of cleaved caspase-3 and Bax proteins while downregulating the level of Bcl-2 and c-myc proteins.